Is Furukara Losing Her Life? : A Reader Responses Analysis in the Translated Novel Convenient Store Woman Written by Sayaka Murata - Laksana, Ketut Gede Adi Putra; Purbani, Widyastuti; Haryati, Isti (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study explores how readers construct meaning and form interpretations of the character Furukara Keiko in the translated novel Convenience Store Woman by Sayaka Murata through a reader-response perspective. Furukara is portrayed as a woman with a “strange” disposition, socially alienated due to her deviation from normative gender expectations. Her refusal to pursue a conventional lifestyle—such as seeking a full-time job, marriage, or motherhood—invites a myriad of reader perceptions that reflect broader socio-cultural negotiations about identity and normality. Adopting a mixed-method approach (Sugiyono, 2020), this research combines content analysis with the theoretical framework of reader-response criticism as formulated by Iser (1978), Fish (1970), and Rosenblatt (1993). Data were collected through stratified random sampling of 400 Goodreads reviews, from which Indonesian-based 50 reviews were purposively selected for their expressive and reflective depth. The analysis draws on seven response strategies by Beach and Marshall in Iskhak (2015): engage, describe, explain, conceive, interpret, connect, and judge. Findings reveal that the most dominant strategy is engagement, indicating strong emotional identification with Furukara’s marginalization and social resistance. Readers often describe her life in their narratives, reimagine her conditions, and relate them to their experiences. The character mirrors and critiques societal norms, particularly concerning gendered expectations (Adawiyah & Hasanah, 2020). This study defines the mutual interaction between reader and text, stress that literary meaning is not fixed but co-constructed through affective, cognitive, and contextual engagements (Priskila, 2024; Purba, 2023). These insights contribute to the growing discourse on gender representation and reader agency in literature.